Cultura profissional e as vivências formativas dos professores da área da saúde - Tonús, Daniela (2017)
This study is part of the Research Line LP1 – Formations, Knowledge and Professional Development of the Post-Graduation Program in Education of the Federal University of Santa Maria (UFSM), Rio Grande do Sul, and had as guiding question: “how the grounded theory can help in the understanding of the repercussions of the professional culture and of the formative experiences in the teaching performance of the professors of the health field? The main goal was to comprehend the rebound of the professional culture and formative experiences in the health field on the professors’ performance. The central concepts of the theoretical reference had as a base one discussion referred to the curricular trajectory of the involved courses and a discussion about the professors’ performance in health and professional culture. For that, it was adopted the qualitative methodology, investigative method that consisted in the substantiated theory, seeking not only to describe data, but also to explain, concept and comprehend a phenomenon from the action and intersection between researcher and participant. The research data was collected from different moments: firstly it was made a conversation with professors in the health field, with the intent of determining the sensitizers concepts. These are useful concepts for the interview script elaboration that was the next step of the data collect. The interviews occurred individually in the Health Science Center (CSS) of UFSM, counting with the participation of a professor representing each course, making it seven participants. The data analysis occurred through the process of codification, beginning with the open codification, then the focused codification and following the process, it was made the axial codification. And, in the end, it was used the selective codification that consists in the elaboration of the substantiated codification. The results characterize the habits, relationship forms and professor’s posture, setting the professional culture of the investigated area. Still, it can be observed that this culture has strong influence in the professors’ performance in class and in other environments of the University. It is important to acknowledge that, the formative experience had fundamental role in the choices and in the professional conduct of the participants, interfering significantly in their convictions, the way they behave and in the way they conduct their interpersonal relationships. The study allowed the comprehension of the fact that the professional culture of the area is a uniform culture, based in beliefs and experiences, with strong influence of the family, the professional practice and the academic formation as a singular way to associate and put critters to the organization of the routine of the University. It is believed that this study can contribute to the acknowledgment of the professors in this area and also of the other areas, generating ideas and the possibility of self-analysis considering the long way of the existed path during the docent trajectory. This way, in the moment that exists this idea, it also exists the chance of changes, improvement and qualification, because recognizing the potentialities and the personal and professional frailties is an important stage of the transformation and actualization process. Still, the results can generate activities that stimulate team actions or qualification courses, contributing for the docent improvement.